Multiphasic Multidetector Computed Tomography Study of a Rare Tracheal Tumor: Granular Cell Tumor - Tommaso Guarnieri; Luciano Cardinale; Gianluca Macchia; Giancarlo Cortese; Andrea Veltri (Case Reports in Pulmonology)
Our aim is to present the case report of a woman affected by tracheal granular cell tumor analysed by multiphasic contrast-enhanced multidetector CT. The tumor presents as polypoid lesion (diameter 13 mm), with smooth and well-defined margins, elevated contrast enhancement in arterial phase, and a modest release of contrast in venous phase. This pattern is quite different from the other tracheal tumours. We have performed a comprehensive review of literature to assess all cases of granular cell tumors of the trachea; only 40 cases are reported. Of these, no one focused on the contrast enhancement aspect, so our work is the first showing a specific pattern in multidetector computed tomography (MDCT) of the tracheal granular cell tumour and may help in differential diagnosis.